An Efficient Root Transformation System for Recalcitrant Vicia sativa - Nguyen, Vy; Searle, Iain R. (Frontiers in Plant Science, 2022)
Common vetch (Vicia sativa) is a multi-purpose legume widely used in pasture and crop rotation systems. Vetch seeds have desirable nutritional characteristics and are often used to feed ruminant animals. Although transcriptomes are available for vetch, problems with genetic transformation and plant regeneration hinder functional gene studies in this legume species. Therefore, the aim of this study was to develop a simple, efficient and rapid hairy root transformation system for common vetch to facilitate functional gene analysis. At first, we infected the hypocotyls of 5-day-old in vitro or in vivo, soil-grown seedlings with Rhizobium rhizogenes K599 using a stabbing method and produced transgenic hairy roots after 24 days at 19 and 50% efficiency, respectively. We later improved the hairy root transformation in vitro by infecting different explants (seedling, hypocotyl-epicotyl, and shoot) with R. rhizogenes. We observed hairy root formation at the highest efficiency in shoot and hypocotyl-epicotyl explants with 100 and 93% efficiency, respectively. In both cases, an average of four hairy roots per explant were obtained, and about 73 and 91% of hairy roots from shoot and hypocotyl-epicotyl, respectively, showed stable expression of a co-transformed marker β-glucuronidase (GUS). In summary, we developed a rapid, highly efficient, hairy root transformation method by using R. rhizogenes on vetch explants, which could facilitate functional gene analysis in common vetch.